2008
DOI: 10.1348/000712607x228474
|View full text |Cite
|
Sign up to set email alerts
|

Chewing gum and context‐dependent memory: The independent roles of chewing gum and mint flavour

Abstract: Two experiments independently investigated the basis of the chewing-gum induced context-dependent memory effect (Baker et al, 2004). At learning and/or recall participants either chewed flavourless gum (Experiment 1) or received mint-flavoured strips (Experiment 2). No context dependent memory effect was found with either flavourless gum or mint-flavoured strips, indicating that independently the contexts were insufficiently salient to induce the effect. This is found despite participants' subjective ratings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…In this sense the present study has failed to replicate our earlier findings (Stephens & Tunney, 2004) and those of other researchers (Wilkinson et al, 2002;Baker et al, 2004, experiment 1;Tucha et al, 2004, experiment 2). However, the absence of enhanced cognitive performance brought about by chewing gum is consistent with other research (Tucha et al, 2004, experiment 1;Allen, Norman, & Katz, 2008;Johnson & Miles, 2008;Smith, 2009a;Smith, 2009b). Nevertheless, chewing gum was shown to be beneficial to performance compared with not chewing on the Digit Span test when a secondary task of counting sounded tones was concurrently performed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this sense the present study has failed to replicate our earlier findings (Stephens & Tunney, 2004) and those of other researchers (Wilkinson et al, 2002;Baker et al, 2004, experiment 1;Tucha et al, 2004, experiment 2). However, the absence of enhanced cognitive performance brought about by chewing gum is consistent with other research (Tucha et al, 2004, experiment 1;Allen, Norman, & Katz, 2008;Johnson & Miles, 2008;Smith, 2009a;Smith, 2009b). Nevertheless, chewing gum was shown to be beneficial to performance compared with not chewing on the Digit Span test when a secondary task of counting sounded tones was concurrently performed.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, Tucha et al (2004) found chewing gum did not enhance participants' immediate and delayed word recall and differentially affected aspects of attention, enhancing sustained attention, showing no effect for divided attention, selective attention, visual scanning and vigilance, and showing decrements in tonic alertness, phasic alertness and flexibility. In addition, recent studies have found no memory enhancement from chewing gum (Smith, 2009a;Smith, 2010), no enhanced learning (Allen, Norman, & Katz, 2008), no improvement in attentional performance (Smith, 2009b) and have not reproduced the context-dependent memory effects that had been observed earlier Johnson & Miles, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…Whether or not gum chewing improves human cognitive function remains an open discussion. Researchers at other laboratories claim that, although gum chewing helps to sustain attention and arousal, it has no effect on learning and memory abilities (63)(64)(65)(66) or even worsens them (67).…”
Section: Does Masticatory Stimulation Facilitate Human Cognitive Funcmentioning
confidence: 99%
“…To what extent might these results be dependent upon shifts in flavour perception, and therefore, salience, between the one gum pellet and four gum pellets conditions? Previous work in our laboratory (Johnson & Miles, 2008) has investigated the potential of flavour in the absence of chewing to provide a sufficiently salient context in free recall. Participants were presented with mint flavour strips in a typical context manipulation experimental design.…”
Section: Discussionmentioning
confidence: 99%